UTILIZATION OF VARIOUS MEDIA FOR MANUFACTURING ORGANOLEPTIC AND HEDONIC QUALITY OF SALTED EGGS - Abdurrahman, Zakaria Husein; Prasetyo, Aris Budi; Jannah, Miftahul; Nostianto, Yohanes (Universitas Veteran Bangun Nusantara, 2025)
This research aimed to determine the addition of strawberry, orange, mango, and chocolate flavors to the organoleptic and hedonic qualities of salted eggs. The experimental design used in this research was completely randomized, with 4 treatments and 25 repetitions. P1 (added strawberry flavor) P2 (added orange flavor) P3 (added mango flavor) P4 (added chocolate flavor). Data analysis was carried out using the Anova test; if treatment was affected, further testing was carried out using Duncan’s Multiple Range Test. From the research results, it can be concluded that the addition of strawberry, orange, mango, and chocolate food flavorings has a real influence on the texture, preference of color, preference of aroma, preference of the texture of the outside of the salted egg, and has a real influence on the texture, choice of the aroma on the inside of the salted egg.